Essays on trade and innovation - Santana, Synthia Kariny Silva de (2016)
The wide availability of data at the firm level in the past twenty years has opened a new range of opportunities for testing important economic theories. In this thesis we aim to explore the complementarity between international trade and investments on innovation in the Brazilian manufacturing industry. In this framework we recognize that innovation is important for firms both because of the positive externalities that it exhibits as with regard to the social returns it provides. For this reason, governments often subsidize these investments, especially the riskiest ones. However, it is still poorly understood how subsidized firms perform over time as we make clear in the first chapter. Although the Economic Subvention Program (ESP) operated by FINEP has aimed at increase innovation activities and the competitiveness of Brazilian companies, the empirical exercise reveals that between 2006 and 2009 there was no significant impact on variables such as productivity, wages per employee, entry/survival in the international market and other relevant policy outcomes. In the second chapter we show that there are gains after entry into the international market for the exporters in the period 1998-2011. Such learning by exporting effects explore innovation as a relevant channel once newly exporting firms have access to inputs, machineries, processes and higher technological standards as those adopted domestically. In the empirical exercise we show that the starters spend significantly more on innovation after entry, compared with extremely similar but essentially domestic firms. The results are robust to several starters categories and are stronger for the period 2004-2008.